Lean Six Sigma Evaluation of Melamine Paint Delivery Quality Performance: Evaluasi Lean Six Sigma terhadap Kinerja Kualitas Pengiriman Cat Melamine - Nurul Amalliyah; Dira Ernawati (Indonesian Journal of Innovation Studies, 2026)
General Background Supply chain quality control is essential for ensuring that distributed products reach customers on time and in acceptable condition. Specific Background Melamine paint delivery involves several packaging types, including bottles, jericans, gallons, and pails, yet shipment defects still occur in the form of leaking gallons, burst gallons, dented pails, and broken bottles. Knowledge Gap Delivery quality studies still require integrated defect measurement and improvement prioritization that combines Lean Six Sigma, Root Cause Analysis, and Analytical Hierarchy Process in finishing material distribution. Aims This study evaluates the sigma level of melamine paint delivery defects and determines prioritized improvement actions to reduce shipment defects. Results Using Lean Six Sigma with the DMAIC approach, the study identified four Critical to Quality categories: leaking gallons, burst gallons, dented pails, and broken bottles. Pareto analysis showed that broken bottles were the dominant defect, with 463 cases or 66% of total defects, followed by dented pails at 15%, burst gallons at 13%, and leaking gallons at 6%. The average DPMO was 20,848, with a sigma level of 3.54. AHP weighting placed broken bottles as the highest-priority CTQ with a weight of 0.62. Novelty This study integrates Lean Six Sigma, RCA, and AHP to measure delivery defects and prioritize corrective actions. Implications Adding plywood bases to truck beds, stacking bottles by size, and arranging paint by delivery sequence can support better shipment quality control. Highlights: One packaging failure type accounted for 66% of total cases. Average DPMO reached 20,848 with a sigma level of 3.54. Top corrective actions focused on truck base protection and loading sequence. Keywords: Analytical Hierarchy Process, Defect, Lean Six Sigma, Melamine Paint, Root Cause Analysis